Impacts of lithologic characteristics and diagenesis on reservoir quality of the 4th member of the Upper Triassic Xujiahe Formation tight gas sandstones in the western Sichuan Basin, southwest China. (September 2019) - Yu, Yu; Lin, Liangbiao; Zhai, Changbo; Chen, Hongde; Wang, Yanan; Li, Yehan; Deng, Xiaoliang
Abstract: The 4th member of the Upper Triassic Xujiahe Formation has become a primary target for tight gas exploitation in the western Sichuan Basin in past decades. Finding relatively high porosity reservoirs in tight sandstones is significant for successful tight gas exploration. In this study, the Xu4 sandstone was studied by a variety of experimental methods, including core observation, thin-section and cathodoluminescence observation, porosity and permeability measurement, mercury intrusion, scanning electron microscopy, X-ray diffraction, electron probe micro-analyzer and fluid inclusion, to determine the reservoir characteristics and also diagenesis evolution and to discuss their impacts on the reservoirs. The Xu4 sandstones are mainly litharenites, feldspathic litharenites and sublitharenites. Among these, calcarenaceous sandstone (CS sandstone) and sandstone with a high kaolinite content (KS sandstone) are classified by their special compositions. The reservoir quality of the Xu4 sandstone is poor, and among the five types of sandstone, the reservoir quality of the KS sandstone is generally better than that of the other types. The diagenetic variations of the Xu4 sandstone are complicated by compaction, kaolinite and quartz cementation, two stages of carbonate cementation, and two stages of dissolution of feldspar and some unstable rock fragments. The KS sandstone is the product of feldspathic litharenite that underwent early-stage dissolution of feldspar during eodiagenesis because of the acidic fluids in the sandstone. This process resulted in a low K + /H + ratio of the pore fluids, i.e., acidic fluids derived from atmospheric fresh water and fluids of adjacent strata bearing coal seams. The determination of the diagenetic evolution indicated that the poor reservoir quality can be attributed to strong compaction or extensive cementation (mainly calcite cementation). However, the occurrence of relatively high porosity reservoirs varies among the sandstones. For CS sandstone, weak early carbonate cementation is essential. For sublitharenite, feldspathic litharenite, and litharenite, late dissolution of feldspar and less cement are necessary for the formation of relatively high-quality reservoirs. Due to their high porosity, almost all of the KS sandstones are relatively high-quality reservoirs. Highlights: Five types sandstone classified based on lithological characteristics. Two stages of carbonate and quartz cementation and dissolution has been undergone. Diagenetic and porosity evolution of various sandstones were established to predict the relatively high-quality reservoir.